Penggunaan Model Pembelajaran Somatic, Auditory, Visualization, Intellectualy (SAVI) dalam Peningkatan Hasil Belajar IPA tentang Organ Pencernaan Manusia Kelas V SD Negeri 3 Dorowati Tahun Ajaran 2020/2021 - Rizki Isnaeni Putri; Suhartono Suhartono; Muhamad Chamdani (Universitas Sebelas Maret, 2021)
The objectives of the research were: (1) to describe the steps of SAVI model in improving natural science learning outcomes, (2) to increase natural science learning outcomes about human digestive system, and (3) to describe the obstacles and solutions in applying SAVI model in improving natural science learning outcomes about human digestive system. The collaborative classroom action research was conducted in two cycles. The subjects were the teacher and 10 students of fifth grade of SDN 3 Dorowati. Data collection techniques were observation, interviews, and tests. The data validity used triangulation of techniques and triangulation of sources. The data analysis included data reduction, data presentation, and conclusions. The results indicated that: (1) the steps of Somatic, Auditory, Visualization, Intellectual (SAVI) model were: (a) preparation stage, (b) delivery stage, (c) training stage, and (d) final stage; (2) the application SAVI model improved natural science learning outcomes about human digestive system to fifth grade students of SDN 3 Dorowati in academic year of 2020/2021; (3) the obstacles were that many students did not cooperate in group discussions and found difficulties in making concept maps. The solutions were that the teacher guided the students to have discussion properly and helped the students in making concept maps.Keywords: Somatic, Auditory, Visualization, Intellectual (SAVI) model, learning outcomes, natural science